2021
DOI: 10.3390/su13020573
|View full text |Cite
|
Sign up to set email alerts
|

When Fact-Checking and ‘BBC Standards’ Are Helpless: ‘Fake Newsworthy Event’ Manipulation and the Reaction of the ‘High-Quality Media’ on It

Abstract: Fact-checking and journalists professional standards usually are considered to be the best fail-safe against manipulations in media. However, we found that newsmakers are able to manipulate even the audience of so-called ‘high-quality media’ who practice all mentioned approaches. To prove this we have refined the concept of ‘pseudo-event’, introduced by D.J. Boorstin, by defining the term ‘fake newsworthy event’ as an event created by newsmakers, that is high-profile and attractive for media, but the only or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…On the other, reputation "persuasiveness" could be useful for coping with the typical free-riding and social-loafing dynamics of social virtual systems. Therefore, a wise use of identifiability features within virtual environments may help in effectively managing online interaction (e.g., Web Projects) [62] and to contrast some dysfunctional dynamics appearing in public information [63].…”
Section: Discussionmentioning
confidence: 99%
“…On the other, reputation "persuasiveness" could be useful for coping with the typical free-riding and social-loafing dynamics of social virtual systems. Therefore, a wise use of identifiability features within virtual environments may help in effectively managing online interaction (e.g., Web Projects) [62] and to contrast some dysfunctional dynamics appearing in public information [63].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, investigating the spread of misinformation, disinformation, fake news, and propaganda in the discourse of Finnish Twitter is a relevant research topic. Previous research has also identified that users have difficulty in recognizing manipulation of information in news [20], which supports the need for further research on the topic. Methods to study and analyze social media data, also regarding misinformation, are currently evolving alongside social media applications.…”
Section: Introductionmentioning
confidence: 61%
“…The only two differences are the lack of objectivity, including the opinion of their author(s) and the value of impact because fake news sites focus on trivial stories [29]. Thus, the recipient, journalist, or reader of a news article usually cannot recognize the manipulation [20].…”
Section: Overview Of Key Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its convenience, people are increasingly seeking out and consuming news through social media. However, the convenience also facilitates the rapid spread and proliferation of fake news [2], which has a devasting impact on individuals and society [3].…”
Section: Introductionmentioning
confidence: 99%